Електронне керування модульним протезом стегна - Стеценко, О. П.; Дацок, О. М. (ХНУРЕ, 2019)
The microprocessor-controlled knee (MPK) improve mobility and reduce the risk injury from falls which leads to better overall health and well-being for transfemoral amputation (TFA) wearers. For them it is important to be able fulfil daily activities without being dependent. The MPK with the sensors helps wearers to be more safety by walking, also on the on the uneven ground, up and down stairs, enhance stumble. The adjustment of knee goes with PC through Bluetooth. The basis mode is already set for walking, other modes can use for other activity, like running, skiing, cycling and much more.
Keywords: стегно; протез модульний; керування електронне